B0 Magnetic Field Conditions in the Human Heart at 3 T Across One Thousand Subjects: A Numerical Simulation Study - Shang, Yun; Theilenberg, Sebastian; Peng, Boyu; Schreiber, Laura M.; Einstein, Andrew J.; Jambawalikar, Sachin R.; Juchem, Christoph (NMR in biomedicine, 2025)
ABSTRACT Functional scans in cardiovascular magnetic resonance (CMR) adopting bSSFP sequences suffer from dark band artifacts due to B0 inhomogeneity. The best remedy to mitigate this issue is through cardiac B0 shimming. The development of an optimal B0 shim strategy for the human heart is hindered by a limited understanding of B0 conditions in clinical diagnostic orientations of CMR. Here, we present high‐resolution B0 distributions in cardiac imaging planes, derived from simulations utilizing high‐resolution computed tomography (CT) images from 1008 subjects, and present an oblique slicing method to derive such B0 distributions. This study also presents a theoretical analysis of spherical harmonic B0 shimming at 3 T using a static global approach and slice‐specific dynamic shim updating in the short‐axis view of human hearts. The characteristics of cardiac B0 conditions along with spherical harmonic shimming were correlated with the subjects' demographic parameters, with weak or no correlations, suggesting limited demographic commonality and predominantly subject‐specific characteristics in cardiac B0. The segmented lung volume shows more significant associations and relatively higher correlations with B0 conditions, indicating that B0 conditions in the heart rely on the anatomy surrounding the heart more than overall body shape and size. This research provides a basis for the development of optimized cardiac B0 shim strategies. We present high‐resolution B0 distributions in cardiac short‐axis views, derived from simulations utilizing CT images of 1008 subjects. A theoretical analysis of spherical harmonic B0 shimming at 3 T was performed, and the B0 conditions were characterized using correlation with demographic parameters to develop optimized cardiac B0 shim strategies.